Pengembangan UMKM Desa Rabakodo: Studi Peluang dan Strategi Usaha Pisang Kembung Goreng - Purnama, Ita; Windari, Kurnia Wardani; Fadyah, Fadyah (CV. Devi Tara Innovations, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, including in the Bima region. This study analyzes opportunities and strategies for the development of Fried Puffy Banana MSMEs in Rabakodo Village through community service activities in the form of training, observation, and business assistance. The results show that there is an increase in product competitiveness through flavor variant innovation, market expansion through digital promotion, and strengthening partnerships with local farmers. This strategy succeeded in increasing production volume by 25% in three months. This study shows the importance of local collaboration in encouraging the sustainability of MSMEs based on village potential.